1999
DOI: 10.1053/euhj.1998.1278
|View full text |Cite
|
Sign up to set email alerts
|

Regional diastolic function in ischaemic heart disease using pulsed wave Doppler tissue imaging

Abstract: Regional diastolic wall motion is impaired at baseline in ischaemic myocardial segments, even when systolic contraction is preserved. Pulsed wave Doppler tissue imaging is a useful non-invasive technique which allows the assessment of regional diastolic performance and dynamics of the left ventricular myocardium. Further studies are required to define this role in the evaluation of coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(97 citation statements)
references
References 27 publications
6
88
0
2
Order By: Relevance
“…Specific cardiac diseases known from TDI measurements that may be suitable for TPM investigations include ischemic cardiomyopathy (2), hypertrophic cardiomyopathy (3), heart trans- plant recipients (4), LV hypertrophy (5), and differentiating constrictive pericarditis from restrictive cardiomyopathy (6). It has been suggested that regional relaxation dysfunction induces a prolongation of the IVR in ischemic cardiomyopathy (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific cardiac diseases known from TDI measurements that may be suitable for TPM investigations include ischemic cardiomyopathy (2), hypertrophic cardiomyopathy (3), heart trans- plant recipients (4), LV hypertrophy (5), and differentiating constrictive pericarditis from restrictive cardiomyopathy (6). It has been suggested that regional relaxation dysfunction induces a prolongation of the IVR in ischemic cardiomyopathy (2).…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic dysfunction accounts for up to half of all heart-failure cases (1). Many experimental studies suggest that regional myocardial relaxation disorders are related to specific cardiac diseases, such as ischemic or hypertrophic cardiomyopathy and LV hypertrophy (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] It is frequently observed in patients with CAD presenting with LV asynergy. [23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography. [26][27][28] Kondo et al have also demonstrated that delayed outward LV wall motion in the isovolumic relaxation phase by digital subtraction high-frame-rate echocardiography was indicative of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The ventricular diastolic filling pattern (E and A waves) is frequently used to represent the ventricular relaxation, which is affected by several factors such as internal loading forces, wall stress, and myocardial contraction. 17 There are many clinical reports of the E-wave velocity and E/A ratio being decreased in patients with ischemic myocardial injury, 18 and of the E-wave velocity being faster for young adults than for older adults (as well as E/A ratio usually also decreasing with age), which may be attributed to reductions of the ventricular compliance and contraction. 25 However, the E-wave velocity and E/A ratio of the zebrafish were increased after partial amputation of the ventricle, which means that myocardial injury appears to promote ventricular diastolic filling.…”
Section: Figmentioning
confidence: 99%
“…Duplex echocardiography including color M-mode imaging (CMI) and pulsed-wave Doppler sonography has been extensively used for diagnosing cardiovascular diseases in human 17,18 and in studies of small animals such as rats and mice. 19,20 Tissue Doppler imaging (TDI) is a relatively new echocardiography technique proposed for the clinical evaluation of the cardiac functions of the human heart.…”
Section: Introductionmentioning
confidence: 99%